Landscape as guiding element in the design and planning of dutch colonial settlements (1600-1800) - Ron Van Oers (Projets de Paysage)
During the period of Dutch overseas expansion (1600-1800) two trading companies, the Dutch East India Company (VOC) and the Dutch West India Company (WIC), founded a large number of cities. These overseas settlements show many resemblances in set-up and lay out. In particular, similarities exist in the chosen locaDtion and functional organisation of the newly established settlement, which aimed to maxi mise the possibilities offered by the surrounding landscape. Unlike Spanish colonisers, for instance, who by using a fixed model with a rigid grid structure largely disregarded the existing terrain, the Dutch favoured flexibility to fully utilize the natural features of the landscape in the needs of the newly founded city. This paper discusses the determinant role of landscape in the planning of Dutch settlements overseas from 1600 to 1800. It first sets out to explain how in general natural elements, traditionally an integral part of the planning process in the Netherlands, were utilised to guide the establishment of colonial cities. ln the second part of the article the argument is further developed and illustrated through the case study of Cape Town in South Africa. The settlement's foundation and development from 1652 onwards is described and analysed utilising seventeenth and eighteenth century Dutch maps as primary sources. It underlines the importance of the surrounding landscape and the large vegetable garden of the Dutch East India Company in guiding the planning, design and development of the city for the next 150 years. Finally, the conclusion considers the implications of this particular planning process for contemporary urban conservation, planning and design. Pointers to further research involving the integration of natural and culturallandscapes in and around Cape Town are appended.